PASSIVE COOLING TECHNOLOGY BY USING SOLAR CHIMNEY FOR MILD OR WARM CLIMATES - Kalkan, Naci; Dagtekin, Ihsan (Vinca Inst Nuclear Sci, 2016)
This study describes the design and analysis of solar system for mild or warm climatic conditions. In order to improve the performance of solar chimney system, well known software FLUENT is used to demonstrate the structures of these systems and finally compare the results with several examples, which have been studied previously. In order to improve the performance of solar chimney system, highly efficient sub-system components are considered for the design. The general purpose of the research is to understand how efficiently solar chimney systems generate cooling, and is to improve the efficiency of such systems for integration with existing and future domestic buildings.
Keywords: active and passive solar technologies; solar cooling system; solar chimney; natural ventilation; cavity depth